Clinical training for the audiology students of International Islamic University Malaysia (IIUM) during the covid-19 pandemic: the challenges vs. opportunities - Rahmat, Sarah; Mohd Sakeri, Nurul Syarida; Rosli, Raihana; Marsudin, Muhammad Rizal; Othman, Nur Hamizah; Ismail, Noor Afzarini Hasnita; Wan Ahmad, Wan Aslynn Salwani (Malaysian National Society of Audiologists, 2021)
Going through this pandemic, the Department of Audiology & Speech Language Pathology (DASLP), IIUM has adapted and devised several methods to help with the students’ clinical training, which includes Tele- Audiology services, virtual external clinical placement, simulated online clinic, online clinical observation and virtual clinical examination